Real time environmental parameter analysis using IOT based platform - Redwan, Md. Azharduddin; Haque, S.M. Ehtesham Ul; Asif, Niaz Mohammad; Shihab, Mamun Abdul Quium (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.